2009
DOI: 10.1002/ppap.200900017
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Discharges in Polar Organic Liquids

Abstract: Electrical discharges in water for pollutant degradation have been studied intensively, but there are almost no studies on electrical discharges in organic solvents. In this study, three separate experiments are conducted in relatively polar organic solvents: diamond-like carbon (DLC) film synthesis, ammonia production, and hydrogen generation from methanol. The synthesis of DLC is attempted by conducting electrical discharge in four different organic liquids: acetone, methanol, acetonitrile, and dimethyl sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…6a). Further confirmation of the thermal origin of the changes inside the plasma channels with a conductivity increase can be found in the manuscript that is under preparation [24] and deals with molecular hydrogen production from water at different conductitvities. In [24], the trend of hydrogen gas formation as a function of conductivity is the same as for that in [19] (hydrogen concentration goes through a maximum, after which it decays to zero with a further conductivity increase) again confirming the connection between conductivity, temperature rise and radical and molecular species distribution.…”
Section: Emission Spectroscopy Measurementsmentioning
confidence: 79%
“…6a). Further confirmation of the thermal origin of the changes inside the plasma channels with a conductivity increase can be found in the manuscript that is under preparation [24] and deals with molecular hydrogen production from water at different conductitvities. In [24], the trend of hydrogen gas formation as a function of conductivity is the same as for that in [19] (hydrogen concentration goes through a maximum, after which it decays to zero with a further conductivity increase) again confirming the connection between conductivity, temperature rise and radical and molecular species distribution.…”
Section: Emission Spectroscopy Measurementsmentioning
confidence: 79%
“…The polarity of the power supply was switched by reversing the position of a rectifier. The rotating spark gap power supply represents a simple and a cheap pulsed power supply that has been efficiently used for various environmental applications in air and water [21,22]. In the present work, the pulsed power was used only for the treatment of spores deposited on the plastic surfaces without water spraying.…”
Section: Discharges Usedmentioning
confidence: 99%
“…Nowadays, microwave or radio-frequency discharge in liquid has been applied in many fields, such as decomposition of waste liquids [23][24][25][26][27], synthesis of nanomaterials [28][29][30][31], deposition of diamond [9], sterilization in medical fields [32], and production of fuel gas [27,33,34]. However, up to now, some fundamental study for microwave discharge in water has been rarely reported [35,36].…”
Section: Introductionmentioning
confidence: 99%